Genome-wide identification and characterization of BASIC PENTACYSTEINE transcription factors and their binding motifs in coconut palm - Lao, Zifen; Mao, Jiali; Chen, Runan; Xu, Ran; Yang, Zhuang; Wang, Ying; Zhou, Junjie; Mu, Zhihua; Xu, Hang; Li, Fengmei; Huang, Dongyi; Xiao, Yong; et al. (Frontiers in Plant Science, 2024)
BASIC PENTACYSTEINE (BPC) is a small transcription factor family that functions in diverse development processes in plants. Although BPC is well-known for binding GA-motif and regulating flower and seed development, there has been rare research in coconut (Cocos nucifera) analyzing their functional characteristics and target genes. In this study, we systematically characterized the gene structure, conserved protein domains, gene expansion, and target genes of CnBPCs in coconut. Eight CnBPCs were identified in the coconut genome, including three CnBPCs in Class I that were derived from triplication of one BPC, four CnBPCs in Class II with CnBPC6A and CnBPC6B derived from segmental duplication, and single CnBPC7 in Class III. Three DNA binding motifs were detected in CnBPCs, which were conserved in most sites but with extensive variation of certain sites. Widespread BPC gene expansion was detected in coconut and other plant species, while only three BPCs were found in the most basal extant flowering plant. The analysis of the GA-motif in the promoter region indicated that 92% of protein-coding genes had at least one, and the (GA) 3 -motif is the most widespread type. Additionally, the GA-motif had the highest occurrence probability within a distance of 1-250 bp distance from the start code. The Y1H assay indicated that genes containing the GA-motif show a high expression correlation with CnBPCs and tend to have a strong interaction with the corresponding CnBPC. Additionally, promoters rich in GA-motif tend to interact with all members of CnBPC. It is suggested that CnBPCs may play a role in seed germination, flower development, and mesocarp development by interacting with genes such as CnAG1, CnAG2, CnSTK, CnMFT, and CnCS.The dual-luciferase assay showed that CnBPCs could activate or repress the transcriptional activities of promoters containing either (GA) 3 -, or (GA) 11 -motifs, but with a bias towards certain genes. We then further constructed co-expressed networks of CnBPCs and identified 426 genes containing GA-motifs that could be targets of CnBPCs. This study characterized CnBPCs' binding motif and possible target genes, laying a theoretical foundation to reveal CnBPCs' function in flower and seed development.